Studi Eksplanatoris tentang Terpaan Iklan “Are You Ready to Try Grammarly” oleh Almeida Kezia terhadap Mahasiswa Strata-1 Fakultas Ilmu Komunikasi Universitas Padjadjaran - Veronika Florita Novarani; Asep Suryana; Frila Nurfadila (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Grammarly is an AI-based tool/application that utilizes YouTube as a platform to upload its advertisement titled "Are You Ready To Try Grammarly." The purpose of this study is to determine the extent of the influence of intensity, message content, and appeal of the YouTube ad "Are You Ready To Try Grammarly" both partially and simultaneously on the interest in subscribing to the product through attitudes toward the ad and brand among students, examined through cognitive response theory. The method used to analyze the data is quantitative and path analysis. The population of this study is undergraduate students of the Faculty of Communication Sciences at Universitas Padjadjaran who have been exposed to the YouTube ad "Are You Ready To Try Grammarly" by Almeida Kezia. The number of respondents in this study is 149, selected using stratified random sampling. Data collection techniques were carried out using questionnaires and literature studies. The results of the study indicate that the intensity, message content, and appeal of the YouTube ad "Are You Ready To Try Grammarly" significantly influence the interest in subscribing to the product through attitudes toward the ad and brand among students both simultaneously and partially. Attitudes toward the ad and brand have the greatest influence on the interest in subscribing.